Transformation of Patent Policy in Indonesia: New Opportunities and Challenges for Pharmaceutical Innovation in the Digital Era - Raymond R. Tjandrawinata; Henry Soelistyo Budi (Pusat Publikasi Nusantara, 2025)
Indonesia is a developing country with an expanding healthcare market, which faces the enduring challenge of fostering a pharmaceutical patent system that incentivizes research and development while ensuring broad access to affordable medicines. This study aims to offer policy recommendations that balance the need for pharmaceutical innovation with the imperative of maintaining an accessible and competitive healthcare landscape. The study includes a review of pharmaceutical patent regulations in India, Brazil, the United States, and the European Union. It integrates empirical data analysis to assess patent application trends and market dynamics, utilizing a difference-in-differences econometric model to establish causality between policy reforms and sector changes. It highlights the necessity of public health safeguards, proposing mechanisms like conditional compulsory licensing as critical elements in the patent reform framework. The study emphasizes actionable policy recommendations while incorporating stakeholder perspectives from regulatory authorities, pharmaceutical firms, and public health organizations to understand the implications for investment, competition, and medicine accessibility. By implementing these strategic policy adjustments, Indonesia can maximize the benefits of Law No. 65 of 2024 while safeguarding public health and promoting domestic pharmaceutical innovation in a rapidly evolving global landscape.